Challenging current interpretation of sunflower movements. (24th August 2019) - van Wyk, Anne S; Prinsloo, Gerhard
Abstract : Several misconceptions may exist in the literature regarding Helianthus annuus L. (sunflower) movements due to the exclusion of the earth's rotation around its own axis, gravity, and gravitation. Abstract: In the literature, Helianthus annuus L. (sunflower) movements are generally described as heliotropic. It is generally believed that the leaves and flowers of the growing H. annuus plant track the sun as the sun moves across the sky from east to west. This paper, however, challenges current interpretation regarding H. annuus movements, as the literature generally excludes the rotation of the earth around its own axis, gravity, and the possible role of gravitation. The general exclusion of the earth's rotation in the literature may also have resulted in flawed research design in studies conducted on H. annuus movements, which in turn may have directed researchers towards the misinterpretation of results. This paper aims to include the possible role of the Earth's rotation, gravity, and gravitation when describing H. annuus movements and to provide possible alternative explanations for the results achieved by researchers. This paper further includes concepts and examples relevant to plant movements, such as the rhythms often associated with plant movements, the physiology of plant movements, referring to turgor pressure as the main force behind plant movements, and plant rhythmic clocks and their characteristics, in order to explain the alternative views and to relate them to H. annuus movements.